2015
DOI: 10.4238/2015.january.15.14
|View full text |Cite
|
Sign up to set email alerts
|

Association of liver X receptor α (LXRα) gene polymorphism and ischemic stroke

Abstract: ABSTRACT. We examined the relationship between the liver X receptor a gene (LXRα) rsl2221497 polymorphism and the susceptibility to ischemic stroke in a Chinese population. The polymerase chain reaction-restriction fragment length polymorphism technique was used to detect the genotype of rsl2221497 in the LXRα gene of 300 stroke patients and 300 healthy control subjects. The chi-square test was used to analyze the genotype distribution between the 2 groups. We found that the risk of stroke in carriers with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, LXRα genetic variation in the LXRα may be associated with susceptibility to stroke. Wang et al pointed out that LXRα the rsl2221497 polymorphism in the LXRα gene can increase the risk of stroke in the Chinese Han population (H. X. Wang et al, 2015). However, although loss‐of‐function studies in LXRα, β (−/−) mice have demonstrated that the effects of LXRs agonists are specific to LXR receptors and that both LXRs isoforms are found in the brain after MCAO, the sepcific role of LXRα and LXRβ in the setting of cerebral ischemia has not been clarified respectively.…”
Section: Roles Of Lxrα In Inflammation‐associated Diseasesmentioning
confidence: 99%
“…In addition, LXRα genetic variation in the LXRα may be associated with susceptibility to stroke. Wang et al pointed out that LXRα the rsl2221497 polymorphism in the LXRα gene can increase the risk of stroke in the Chinese Han population (H. X. Wang et al, 2015). However, although loss‐of‐function studies in LXRα, β (−/−) mice have demonstrated that the effects of LXRs agonists are specific to LXR receptors and that both LXRs isoforms are found in the brain after MCAO, the sepcific role of LXRα and LXRβ in the setting of cerebral ischemia has not been clarified respectively.…”
Section: Roles Of Lxrα In Inflammation‐associated Diseasesmentioning
confidence: 99%